Parent of origin genetic effects on methylation in humans are common and influence complex trait variation - Yanni Zeng (Nature Portfolio, 2019)
Parent-of-origin effects (POE) are observed when there are different effects from alleles inherited from the two parents on phenotypic measures. Here, Zeng et al. study POE on DNA methylation in 5,101 individuals and identify genetic variants that associate with methylation variation via POE and their potential phenotypic consequences.